PERSPEKTIF MAHASISWA TERHADAP AKSES FASILITAS DAN LAYANAN PERPUSTAKAAN UNIVERSITAS TIDAR - ibad, asna choirul (Saraq Opat: Jurnal Administrasi Publik, 2025)
This study is based on the importance of the role of libraries in supporting students' academic activities, especially in the digital era. The aim is to determine the perception of Public Administration students regarding access and quality of Tidar University Library services, both physically and digitally. This study uses a quantitative method with a survey approach and purposive sampling technique. Data were collected through a questionnaire with a Likert scale. which includes aspects of staff friendliness, ease of borrowing, comfort of the reading room, and effectiveness of the online catalog. The results showed that most students were satisfied with the services provided, especially regarding the attitude of the staff and the efficiency of borrowing. Good access to physical and digital facilities also encourages the frequency of use of library services. These findings emphasize the importance of developing digital services to support the ever-growing academic needs. Libraries need to continue to innovate in order to create an inclusive and adaptive learning environment to technological advances.